Fuzzy logic controller-based Luo converter for light electric vehicles - Rangaswamy Balamurugan; Komarapalayam Subramaniam Vairavel; Marimuthu Kalimuthu; Veerappan Kiruthiga Devi (Institute of Advanced Engineering and Science, 2024)
A brushless DC motor (BLDC) drive fed by a Luo converter is presented in this paper for the use in electric vehicle (EV) applications. The proposed Luo converter provides stable and ripple free output for EV. An approach for getting the stable output voltage is by using a fuzzy logic controller to control the Luo converter. It helps to generate the appropriate pulse with respect to the feedback voltage. This proposed system has the advantages like voltage increase, high-gain output with low ripples and high efficiency. The performance of this proposed drive is tested through hardware prototype at varying line voltage levels and results are demonstrated. A comparative analysis is presented to justify the effectiveness of the proposed Luo converter fed EV motor.